La première mondialisation. Quelle place pour l’Afrique dans l’histoire évolutive et biogéographique du genre Homo ? - Jean-Renaud Boisserie (Afriques)
Africa hosted our evolution till the appearance of the genus Homo and its spreading over Eurasia about two million years ago. What happened afterwards? Did the following episodes take place in Eurasia, as suggested by the phrase “out of Africa” used to describe this conquest? The main phases of this “exit” are briefly described by using fossil, archeological, and genetic data; and alternative hypotheses, recapitulated. Africa apparently remained the center of innovation and dispersal in human evolutionary history up till a few tens of thousand years ago.